ANALYSIS OF THE INFLUENCE OF PERCEPTIONS OF BENEFITS, EASE OF USE, AND RISKS ON DECISIONS TO USE ELECTRONIC MONEY BASED ON QUICK RESPONSE CODE INDONESIAN STANDARD - Annisa, Alifah; Syarifuddin, Syarifuddin; Rura, Yohanis (Contemporary Journal on Business and Accounting, 2023)
Purpose – This study aims to find out and analyze how much effect the application of perceived benefits, ease of use, and risk has on the use of the Indonesian standard quick response code Design/methodology/approach – This research uses a quantitative approach and the method used is multiple linear regression analysis. Sample determination is carried out by purvosive sampling method Findings – The results of this study indicate that in the millennial generation sample, perceived ease of use affects the decision to use electronic money based on the Indonesian standard quick response code. However, perceived of usefulness and risks have no effect. Meanwhile, in the merchant sample, perceived of usefulness, ease of use, and risk have no effect on the decision to use electronic money based on the Indonesian standard quick response code and there is an average difference between the millennial generation and merchant sample groups. Originality – The number of samples used in this study was 80 respondents who were in Makassar City. Keywords: Perceived, Decision on Use, Quick Response Code Indonesian Standard Paper Type Research Result